2021
DOI: 10.3389/fpsyg.2021.806587
|View full text |Cite
|
Sign up to set email alerts
|

Students' Learned Helplessness and Teachers' Care in EFL Classrooms

Abstract: The construct of learned helplessness, as one of the noticeable emotional issues in education, has been investigated and approved its prominent place in education for its stimulus on students' accomplishment, enthusiasm, and commitment in learning. Moreover, the role of teachers as the most crucial issues in the learning viewpoint is at the center of attention since they help learners to be more motivated and provide a supportive context by caring. So, the current review of literature tries to emphasize teache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
(30 reference statements)
0
1
0
Order By: Relevance
“… 6 The essence of LH is a learned negative motivation. 7 It has been demonstrated that LH significantly impacts self-management and adherence in MHD patients. 8 , 9 Patients with high LH are not confident in their ability to control disease and manage their lives and are prone to negative expectations.…”
Section: Introductionmentioning
confidence: 99%
“… 6 The essence of LH is a learned negative motivation. 7 It has been demonstrated that LH significantly impacts self-management and adherence in MHD patients. 8 , 9 Patients with high LH are not confident in their ability to control disease and manage their lives and are prone to negative expectations.…”
Section: Introductionmentioning
confidence: 99%